2017
DOI: 10.3390/app7050462
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Origin of Polyamide 12 Powder on the Laser Sintering Process and Laser Sintered Parts

Abstract: Different features of polymer powders influence the process of laser sintering (LS) and the properties of LS-parts to a great extent. This study investigates important aspects of the "powder/process/part"-property relationships by comparing two polyamide 12 (PA12) powders commercially available for LS, with pronounced powder characteristic differences (Duraform ® PA and Orgasol ® Invent Smooth). Due to the fact that the primary influence factor on polymer behaviour, the chemical structure of the polymer chain,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 16 publications
3
51
0
Order By: Relevance
“…These results show that the melt emulsification process is exceptionally suited to produce particles with sizes and shapes that resemble and even surpass commercially used laser sintering materials. As demonstrated in [15][16][17][18][19], the particle shape to a large extent determines the flowability and packing density of the powder, and in this way the density and mechanical properties of produced parts. The favorable shape of the current PBT powder permits the production of dense, mechanically stable parts.…”
Section: Particle Morphology and Shapementioning
confidence: 99%
See 3 more Smart Citations
“…These results show that the melt emulsification process is exceptionally suited to produce particles with sizes and shapes that resemble and even surpass commercially used laser sintering materials. As demonstrated in [15][16][17][18][19], the particle shape to a large extent determines the flowability and packing density of the powder, and in this way the density and mechanical properties of produced parts. The favorable shape of the current PBT powder permits the production of dense, mechanically stable parts.…”
Section: Particle Morphology and Shapementioning
confidence: 99%
“…It was found that in general, a smooth and spherical particle shape contributes to the laser sintering material performance. In a comparison of two laser-sinterable PA12 powders, Schmid et al [19] found increased tensile strength and elongation at break for the powder with the higher sphericity. This was attributed at least partially to the improved packing density achieved with spherical particles.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The laser sintering of PA12 is a manufacturing process where a solid body is created out of an unstructured and formless powder bed using focused laser power. This means that besides the shape, the properties of the part will also be created to a certain extent during the manufacturing process [53]. Accordingly, the properties of the processed material are as listed in Table 2.…”
Section: Manufacturingmentioning
confidence: 99%